Hadith #3420 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; al-Sa'ib bin Yazid bin Akht Namr; Ibrahim bin 'Abdullah bin Qariz إبراهيم بن عبد الله بن قارظ; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Rafi' bin Khadij bin Rafi'; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
You have brought what is good from this man. Then they brought a lunatic in chains. He recited Surat al-Fatihah over him three days, morning and evening. When he finished, he collected his saliva and then spat it out, (he felt relief) as if he were set free from a bond. They gave him something (as wages). He then came to the Prophet (ﷺ) and mentioned it to him. The Messenger of Allah (ﷺ) said: Accept it, for by my life, some accept it for a worthless charm, but you have done so far a genuine
Grade: Sahih